Production of pepper and industrial tomato seedlings fertilized with biostimulants (Research, Society and Development, 2021)
Growth regulators such as biostimulants can promote positive changes in the plant physiological processes, being alternatives to help the seedlings development with high seedlings quality. Therefore, this study aims to evaluate the characteristics of industrial tomato and pepper seedlings fertilized with biostimulants. The experimental design was a randomized block design with six treatments and four replicates. The treatments were: fertilizers with different nutrient compositions, being, T1: formulated mix containing N, P and K, using as sources urea, monoammonium phosphate, and potassium chloride respectively; T2: biostimulant 1 with auxin; T3: biostimulant 2 with fulvic acids and inositol; T4: biostimulant 3 with organic carbon; T5: zinc sulfate, and T6: distilled water (control). Root length and root dry mass were not affected by the treatments applied in pepper and tomato seedlings. Stem diameter, length, and dry mass, and the number of leaves were superior in pepper when NPK or zinc sulfate was applied. The same variables were superior in industrial tomato when NPK or biostimulant 3 (organic carbon) was applied. The results found indicated that amendments can be used to produce more vigorous pepper and industrial tomato seedlings.